QCA-BASED design of reversible hamming code encoding, decoding and correcting circuits - Galadima, Bahijja Yahaya; Shehu Musa Galadanci , Garba (International Journal of Basic and Applied Sciences, 2024)
This work proposes a model of a low-power hamming code generator (HCG) circuit for single-bit data with 11 cells, based on a reversible Feynman gate. A circuit is implemented for error detector parity bit (EDP) in hamming coding for message signals of three bits with 21 cells. To ensure optimum functionality, the suggested circuits and their theoretical values are verified using the QCA Designer simulator version 2.0.3, and the energy dissipation of the circuits is estimated using the QCA Designer-E. The results for the simulation show that the proposed circuits improve the occupied area by 82.5% and the cell counts by 66.6% for the HCG circuits. Additionally, the EDP circuit improves the occupied area by 55% and the cell counts by 25%. The error-correcting circuit with coplanar crossover achieves 30.5% in the occupied area and 16.7% cell reduction. The result also proves that energy dissipation by the proposed circuit increases as the cell count increases. As such, the cell count, area, and energy dissipation performance are all greatly improved by the proposed Hamming coding circuit. This shows that QCA-based reversible circuits are more energy-efficient, quicker, and denser than other types, which makes them a good option for usage in upcoming nanoscale integrated circuit applications.